LEGISLATIVE PREREQUISITES FOR THE IMPLEMENTATION OF MANDATORY ACCUMULATIVE PENSION INSURANCE IN UKRAINE - Zvarych, O. I.; Voloshyn , V. V. (The actual problems of regional economy development, 2024)
One of the priority directions for overcoming social injustice in modern society is decent pension provision, which is a type of social guarantees provided by the state to its citizens and must be protected by domestic legislation. Thus, legislative and regulatory acts are important tools regulating relations between the state and its citizens in the field of pension insurance. Taking into account the fact that for many years mandatory accumulative pension insurance is only at the stage of discussion, and the lack of a reliable legislative framework only hinders its introduction, therefore the topic discussed in this article remains relevant and requires further study. The purpose of the study is to systematize and characterize the accumulative pension insurance by studying the legal aspects of the implementation of its mandatory component. Since, the modernization of the national legislation regarding the operation of mandatory accumulative pension insurance will allow to unify the pension system and improve the pension provision in old age for the future generations of pensioners. Considering the fact that the pension legislation underwent changes over time and was constantly under the determining influence of the evolution of national development, the historical method was used as the methodology of this study. At the same time, in order to form appropriate conclusions regarding the legislative and legal framework of pension provision and to study its evolution and development prospects, the article uses systemic and synergistic approaches, as well as methods of analysis and synthesis, induction and deduction, comparative and content analysis. The article highlights the study of legislative aspects of the introduction of mandatory accumulative pension insurance in Ukraine, analyzes its legal framework, considers the main changes and their impact on pension provision, in particular on its accumulative component, outlines the main prospects for further improvement and development. It has been established that regulatory and legal regulation of accumulative pension insurance is an important factor both for increasing the trust of citizens and improving their standard of living after retirement, and for maintaining the stability of the pension system and providing the state with a source of long-term investment resources. It was determined that the urgent need of the hour and a necessary condition for the existence of an effective and just system of pension relations in the field of social security of citizens is the creation of legislative prerequisites for the functioning of accumulative pension insurance, since only legislative acts can be those important instruments that carry out the appropriate regulation of the state’s legal relations with by their citizens. The study showed that for the successful implementation of mandatory accumulative pension insurance, which will form a model of the second level of the pension system in Ukraine, it is necessary to create appropriate legislative prerequisites. In addition to the already existing legislative documents in the field of pension provision, it is also necessary to develop a complete set of normative legal acts that will regulate all issues related to the effective functioning of the mechanism of the accumulative pension insurance system. The introduced new legislative documents should become a legal basis and incentive for the working population to participate in accumulative pension programs, which will be a powerful source of investment for the national economy and contribute to its further development and growth. The adopted legal framework will serve as a reliable protective mechanism and strengthen the trust of citizens, become a guarantee, and guarantee of the safety of saving and investing accumulated pension funds, ensure compliance with all obligations, provide protection against mistakes and prevent abuse and violations of financial discipline. Improved pension legislation should also ensure effective state supervision and public control over the issues of accumulative pension provision, as well as be a reliable mechanism for realizing and guaranteeing the right to receive accumulative pension benefits.